Aplikasi Game Balap Sepeda Ontel Berbasis Android - Muh. Rifli Aris; Ade Hastuty; Mughaffir Yunus; Muhammad Basri; Ahmad Selao (Politeknik Kampar, 2025)
Traditional games are part of cultural heritage that contain historical and educational values. One example is the ontel bicycle, a classic bicycle still widely known among Javanese people as the